(untitled) (The Research of Medical Science Review, 2025)
Coronaviruses are associated with severe illness, severe epidemics, and death in humans and animals belonging to the subfamily Coronavirinae of the family Coronaviridae. Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS) were important examples of zoonotic coronaviruses. Rodents are the largest order of mammals composed of more than 2000 species, representing more than 40% of all mammalian species. Rodents are the major zoonotic source of human infectious diseases; they often live at high densities and hence may harbor high levels of microbial diversity. This study aimed to assess the prevalence of coronaviruses in rodent populations in Bahawalpur, Pakistan using improved detection methods through reverse transcription PCR (RT-PCR). Between February and June 2024, we humanely captured 59 rats and collected the fecal swabs for analysis. We specifically targeted the RNA-dependent RNA polymerase gene with RT-PCR to increase sensitivity. According to our results, eleven of the sampled pools tested positive for coronaviruses. Results imply the prevalence of coronaviruses in the population of rats in the Bahawalpur and their significant role in zoonotic transmission. These results indicate addressing wildlife surveillance to monitor coronaviruses prior so that the possibility to occur unknown outbreaks due to coronavirus can be reduced, but also infectious diseases as well.